2021
DOI: 10.1680/jcoma.19.00056
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of porous asphalt with reclaimed asphalt, dune sand and lime

Abstract: A porous asphalt pavement is an open-graded asphalt mix that allows rainwater to drain through the surface layer. When designing a pavement structure, the porous asphalt layer is generally not taken into consideration due to its poor mechanical characteristics. The objective of this research study was to reuse reclaimed asphalt pavement in a porous asphalt mixture and then to improve the performance of the resulting mix by adding dune sand and lime. Several porous asphalt mixes with the addition of different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The strength differential might be more than 10%, depending on the DS/FA ratio [ 34 ]. Since the compressive capacity has greatly increased and the tensile strengths have only marginally diminished, it was possible to create a material that may be considered when constructing pavement constructions by adding dune sand and lime to permeable asphalt [ 49 ]. At all evaluated ages up to 44 percent, the recycled aggregate made from concrete waste used to make the dune sand mortar had lower tensile strength than the specimen mortar.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…The strength differential might be more than 10%, depending on the DS/FA ratio [ 34 ]. Since the compressive capacity has greatly increased and the tensile strengths have only marginally diminished, it was possible to create a material that may be considered when constructing pavement constructions by adding dune sand and lime to permeable asphalt [ 49 ]. At all evaluated ages up to 44 percent, the recycled aggregate made from concrete waste used to make the dune sand mortar had lower tensile strength than the specimen mortar.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…Despite its advantages, RAP is still considered as waste and is rarely used in road construction in North African countries [24][25][26]. This work is a continuation of previous investigations that have aimed to better prediction of the viscoelastic behavior of asphalt mixtures incorporating high RAP content, and other additions such as dune sand and lime [13,17,19,20]. In this paper, a new formula that contains 40% of RAP, 10% of dune sand and 1% of hydrate lime is proposed and tested to evaluate its mechanical behavior and compare it to that of the conventional mixes.…”
Section: Introductionmentioning
confidence: 95%
“…They have also concluded that the addition of 10% of dune sand to the asphalt mixes containing 40% of RAP can significantly improve the mechanical characteristics of the mixtures in terms of Marshall stability and flow, water resistance, and compaction behavior [20]. However, they revealed in a later study a small decrease in the splitting tensile strength of mixtures containing high RAP and dune sand compared to the conventional mixtures [13].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations